Susceptibility to Mycobacterium ulcerans Disease (Buruli ulcer) Is Associated with IFNG and iNOS Gene Polymorphisms - Bibert, Stéphanie; Bratschi, Martin W.; Aboagye, Samuel Y.; Collinet, Emilie; Scherr, Nicole; Yeboah-Manu, Dorothy; Beuret, Christian; Pluschke, Gerd; Bochud, Pierre-Yves (Frontiers in Microbiology, 2017)
Buruli ulcer (BU) is a chronic necrotizing disease of the skin and subcutaneous fat tissue. The causative agent, Mycobacterium ulcerans, produces mycolactone, a macrolide toxin, which causes apoptosis of mammalian cells. Only a small proportion of individuals exposed to M. ulcerans develop clinical disease, as surrounding macrophages may control the infection by bacterial killing at an early stage, while mycolactone concentration is still low. Otherwise, bacterial multiplication leads to in higher concentrations of mycolactone, with formation of necrotizing lesions that are no more accessible to immune cells. By typing a cohort of 96 Ghanaian BU patients and 384 endemic controls without BU, we show an association between BU and single nucleotide polymorphisms (SNPs) in iNOS (rs9282799) and IFNG (rs2069705). Both polymorphisms influence promoter activity in vitro. A previously reported SNP in SLC11A1 (NRAMP, rs17235409) tended to be associated with BU. Altogether, these data reflect the importance of IFNG signaling in early defense against M. ulcerans infection.